Ambiguitas Informasi pada Pengambilan Keputusan Audit - Siti Rahayu; Intiyas Utami (Jurnal Akuntansi dan Bisnis, 2016)
The aim of this research is to examine the impact of ambiguity information in the decision making audit. This study used factorial experiment method 1 x 2 between subjets with 72 participants of the undergraduate Accounting students. The data was analyzed by using independent t-test and analysis of variance (ANOVA). In this study, information ambiguity were manipulated into three levels: insufficient/complex; sufficient/complex; sufficient/not complex. The result shows that ambiguity level had a negative effect on the accuracy of audit decision. The empirical evidence provided that insufficient/complex data cause infomation ambiguity and impact to the auditor’s inaccurate in decision-making.